2023
DOI: 10.1111/jmcb.13041
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the LTV Ratio: Lending Standards, Regulatory Arbitrage, and Mortgage Default

Abstract: Booming house prices are historically correlated with loose lending standards. Nonetheless, in Spain the loan‐to‐value (LTV) ratio failed to capture imbalances during the last housing boom. Using loan‐level data from millions of mortgages we show that inflated collateral valuations, used by banks as a mechanism to circumvent regulation, distorted the informative value of LTV, and masked the accumulation of risk. We identify that regulation relying upon a single measure is more prone to suffer from regulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…The insight that secondary mortgages are riskier than single loans is also in line with those of Kelly and O'Toole (2018) and Galán and Lamas (2019), who find multi-loan borrowers and second-home properties to have a higher chance of default. Our policy message on restricting LTVs for secondary mortgage takers is compatible with the agent-based model conclusion of Tarne and others (2022), which states that differentiation of BBM limits to different classes of borrowers may be welfare-improving.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The insight that secondary mortgages are riskier than single loans is also in line with those of Kelly and O'Toole (2018) and Galán and Lamas (2019), who find multi-loan borrowers and second-home properties to have a higher chance of default. Our policy message on restricting LTVs for secondary mortgage takers is compatible with the agent-based model conclusion of Tarne and others (2022), which states that differentiation of BBM limits to different classes of borrowers may be welfare-improving.…”
Section: Discussionsupporting
confidence: 60%
“…This is also supported by other research papers, including that of Kelly and O'Toole (2018), who show that multi-loan borrowers have a higher default risk, even after controlling for the DSTI ratio and other borrowerloan characteristics. Adding to this, Galán and Lamas (2019) find that mortgages on second-home properties have a higher PD. Further, secondary mortgages are riskier, because they are not taken out by first-time buyers, who are known to be low-risk borrowers, as found by Kelly and others (2015), Mihai andothers (2018), andothers (2019), among others.…”
Section: Secondary Mortgagesmentioning
confidence: 74%
See 2 more Smart Citations
“…Earlier studies have found appraisals to be upwardly biased (Calem et al, 2021) and that a need to refine costly unsecured debt (Reite et al, 2022), a steady increase in real estate prices (Galán and Lamas, 2023), and competition between banks (Conklin et al, 2020) can contribute to such bias. We hypothesize that government-mandated LTV policies may increase incentives to upwardly bias valuations by systematically choosing the less conservative valuations available.…”
Section: Introductionmentioning
confidence: 99%